2013
DOI: 10.1172/jci62839
|View full text |Cite
|
Sign up to set email alerts
|

Signaling effectors underlying pathologic growth and remodeling of the heart

Abstract: Cardiovascular disease is the number one cause of mortality in the Western world. The heart responds to many cardiopathological conditions with hypertrophic growth by enlarging individual myocytes to augment cardiac pump function and decrease ventricular wall tension. Initially, such cardiac hypertrophic growth is often compensatory, but as time progresses these changes become maladaptive. Cardiac hypertrophy is the strongest predictor for the development of heart failure, arrhythmia, and sudden death. Here we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
364
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 389 publications
(371 citation statements)
references
References 162 publications
(127 reference statements)
4
364
1
2
Order By: Relevance
“…The in vivo staining of zebrafish embryos at 2 dpf with MitoSOX Red revealed the presence of high levels of ROS in the hearts of Tom70 morphants compared with MO-ctrl ( Figure 5G). We also measured the expression levels of a regulated set of genes involved in cardiac hypertrophy, including ANP, α-MHC and GATA4 [16,17], in the morphant hearts. As shown in Figure 5H, the inactivation of Tom70 increased the expression of ANP and reduced the expression of α-MHC and GATA4.…”
Section: Oxidative Stress Mediates Tom70 Deficiency-induced Cardiomyomentioning
confidence: 99%
“…The in vivo staining of zebrafish embryos at 2 dpf with MitoSOX Red revealed the presence of high levels of ROS in the hearts of Tom70 morphants compared with MO-ctrl ( Figure 5G). We also measured the expression levels of a regulated set of genes involved in cardiac hypertrophy, including ANP, α-MHC and GATA4 [16,17], in the morphant hearts. As shown in Figure 5H, the inactivation of Tom70 increased the expression of ANP and reduced the expression of α-MHC and GATA4.…”
Section: Oxidative Stress Mediates Tom70 Deficiency-induced Cardiomyomentioning
confidence: 99%
“…To elucidate these possible mechanisms, we first investigated the expression and activity of mitogen‐activated protein kinase (MAPK) signaling molecules, as the MAPK pathway is known to play a fundamental role in pathological cardiac hypertrophy 3, 5. Compared with the sham operation, pressure overload by AB operation caused an increase in phosphorylation of MAPK signal pathway members.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the molecular mechanism by which ADAM23 mediates its effects on cardiac hypertrophy, we first examined the MAPK signaling pathway, a pivotal role in the development of cardiac hypertrophy 3. Unexpectedly, we found that MAPK activities were affected by neither ADAM23 deficiency nor overexpression, which indicated that the anti‐hypertrophic effects of ADAM23 were independent of MAPK signaling.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations